2010
DOI: 10.1177/112972981001100211
|View full text |Cite
|
Sign up to set email alerts
|

Proximalization of the Arterial Inflow (PAI) in Patients with Dialysis Access-Induced Ischemic Syndrome: First Report on Long-Term Clinical Results

Abstract: Based on our experience, clinical long-term results are successful in certain patients with DAIIS. The aim for the near future should be a better patency rate to minimize the need for reoperations. In cases of extended limb necrosis/gangrene results were poor. In such patients primary closure of the access must be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The success rate (complete regression of symptoms) was 84% and only mild rest symptoms in 13% of patients were reported. These excellent results were also confirmed in a study published by Thermann et al 13 They reported an 82% success rate in 40 patients. These data demonstrate nearly identical rates of symptom relief to the well-known results of the DRIL procedure.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The success rate (complete regression of symptoms) was 84% and only mild rest symptoms in 13% of patients were reported. These excellent results were also confirmed in a study published by Thermann et al 13 They reported an 82% success rate in 40 patients. These data demonstrate nearly identical rates of symptom relief to the well-known results of the DRIL procedure.…”
Section: Discussionsupporting
confidence: 88%
“…A subgroup analysis revealed the inferior performance of non-heparinized versus heparinized grafts, with 31% versus 75%, respectively, after 12 months. 13 The functional patency of the modified PAI fistulas was similar to that of Zanow. However, KaplaneMeier analysis of a small cohort cannot be used.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In two further studies by Thermann et al, PAI was reviewed in 23 and 36 patients respectively [ 18 , 19 ]. In their early series, complete resolution of symptoms was achieved in 65% of patients and improvement seen in 26% with secondary patency of 85% at 18 months.…”
Section: Surgical Managementmentioning
confidence: 99%